ANALISA GERAK TARI DALAM FILM SEKALA NISKALA - I Gusti Ngurah Krisna Yoga; Yulinis Yulinis; I Wayan Budiarsa (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2022)
Sekala Niskala tells the story of a twin brotherhood between Tantri and Tantra, who were born and live in a village in Bali. They have a relationship with the unseen and the full moon. Tantri, is a Tantric twin who has to be hospitalized due to a disease that is eating away at his brain abilities. This research was conducted to analyze the variety of dance movements in the film Sekala Niskala. From the above phenomena described, there are problems that exist in this writing, including: How did the creation of dance movements in the film Sekala Niskala originate? How is the analysis of dance movements in the film Sekala Niskala? The research method used is descriptive qualitative research method to solve this research problem. found in field observations, interviews, literature studies, documentation. The theoretical basis used in this study is the aesthetic theory in this study which is used to examine the elements, namely form, weight, and appearance related to the Analysis of Dance Motion in the Sekala Niskala Film which analyzes dance movements. Choreographers try to find inspiration for dances that are associated with nature, the environment, animals, plants, art, culture, and Balinese myths. Which in it like the movement of the chicken character, the butterfly character, the monkey character, the tonya character. Of the four character movements, there are several elements to analyze the movement, namely Material, Energy, Space and Time. Keywords: Dance Movement Analysis, Sekala Niskala.